High-performance mould-proof release agent for concrete and preparation method thereof

By using dimethyl silicone oil, hydrogen-containing silicone oil, paraffin and other ingredients in the concrete release agent, and using emulsifier compound and inulin-modified hydrogen-containing silicone oil, the problem of poor stability of the release agent is solved, and efficient long-term storage and excellent antibacterial and anti-mold effect is achieved.

CN119799405APending Publication Date: 2025-04-11SHANDONG HI-SPEED NEW BUILDING MATERIALS CO LTD +2

Patent Information

Application Number
CN202510014551.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing concrete release agents have poor stability during storage and use, prone to stratification, and are not suitable for long-term storage.

Method used

A high-performance anti-mold release agent is adopted, including dimethyl silicone oil, hydrogen-containing silicone oil, paraffin, emulsifier, anti-mold agent, reinforcement components and thickener. Through the combination of emulsifier and the use of inulin modified hydrogen-containing silicone oil, the stability and uniformity of the emulsion are improved, and the anti-bacterial and anti-mold effect is improved through nanosilver sol and alkyl glycosides.

Benefits of technology

The long-term storage stability of the mold release agent is achieved, and it is not prone to deterioration or stratification, which improves the stability and uniformity of the emulsion, and enhances the antibacterial and anti-mold effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of additives for concrete, and particularly discloses a high-performance mould-proof release agent for concrete and a preparation method of the high-performance mould-proof release agent. The high-performance mould-proof release agent for concrete comprises the following raw materials in parts by weight: 10-20 parts of dimethyl silicone oil, 10-20 parts of hydrogen-containing silicone oil, 4-8 parts of paraffin, 2-4 parts of an emulsifier, 1-4 parts of a mould inhibitor, 3-5 parts of a reinforcing component, 2-5 parts of a thickening agent and 30-50 parts of water, the emulsifier is prepared from the following raw materials in percentage by mass: 23.5 to 25 percent of Span-80, 21 to 23 percent of dodecyl benzene sulfonic acid triethanolamine salt and the balance of OP-10. The release agent has the advantages of being good in storage stability, not prone to deterioration and layering, good in release effect, long-acting in antibacterial property and capable of enabling concrete test blocks to be high in strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete additives, and more specifically, to a high-performance anti-mildew release agent for concrete and a preparation method thereof. Background Art

[0002] Precast concrete components are building components made in advance in factories with concrete as the basic material, including beams, slabs, columns and building decoration accessories, etc., for assembly on the construction site, and are the material basis of building industrialization. It has the following characteristics: 1. Good structural performance. Factory production can effectively ensure the mechanical properties of the structure, with small discreteness, especially for the production of standard shaped components. The construction conditions of the precast component factory are stable, the construction procedures are standardized, and it is easier to ensure quality than cast-in-place components. 2. Fast construction speed, can prepare for the construction in advance, and install the precast components that have reached the strength during construction, which can speed up the progress of the project and reduce the labor intensity of workers. 3. Factory production is energy-saving, environmentally friendly, and reduces the noise of on-site construction. 4. It can realize batch industrial production, save materials, and reduce construction costs. The demoulding of precast components is inseparable from efficient and professional concrete release agents.

[0003] Concrete release agent, also known as concrete isolation agent or demoulding lubricant, building formwork release agent, is a substance applied to the inner wall of the building formwork to play a lubricating and isolating role, so that the concrete can be smoothly separated from the formwork when the form is removed, keeping the shape of the concrete intact. Compared with the traditional demoulding material engine oil or waste engine oil, the release agent has the advantages of easy demoulding, no pollution to the concrete surface, no corrosion to the formwork, simple application, and low price.

[0004] In the prior art, a Chinese invention patent document with application number CN201310419154.X discloses an oil-based solid release agent, which is prepared by the following substances in parts by weight: 80-85 parts of base material, 0.8-1.2 parts of emulsifier, 5-10 parts of film-forming aid, 5-15 parts of additive, 5-15 parts of moisture absorbent, and 1-5 parts of antioxidant; the base material contains animal oil, vegetable oil and mineral oil, and soap; the additive is a composite additive, containing high-carbon hydrocarbon, alcohol and alkali, and the high-carbon hydrocarbon is paraffin, and its amount is 5% of the amount of the base material.

[0005] The emulsified oil-based release agents mentioned above have a high emulsification temperature, require a large amount of emulsifier, and the produced emulsified oil has poor stability and is prone to stratification, making it unsuitable for long-term storage. Summary of the invention

[0006] In order to make the release agent have long-term storage stability and not easy to deteriorate or delaminate, the present application provides a high-performance anti-mildew release agent for concrete and a preparation method thereof.

[0007] In the first aspect, the present application provides a high-performance mildew-proof release agent for concrete, which adopts the following technical solution: A high-performance mildew-proof release agent for concrete comprises the following raw materials in parts by weight: 10-20 parts of dimethyl silicone oil, 10-20 parts of hydrogenated silicone oil, 4-8 parts of paraffin wax, 2-4 parts of emulsifier, 1-4 parts of mildew-proof agent, 3-5 parts of reinforcing component, 2-5 parts of thickener and 30-50 parts of water, wherein the emulsifier comprises the following raw materials in parts by weight: 23.5-25% of Span-80, 21-23% of triethanolamine dodecylbenzenesulfonate and the balance of OP-10.

[0008] By adopting the above technical scheme, dimethyl silicone oil can form a uniform film on the template and a separation layer on the template surface, thereby reducing the friction and adhesion between the mold and the concrete. Paraffin wax can effectively reduce the adhesion of concrete on the mold surface due to its lubricity and hydrophobicity, making it easier for concrete to be released from the mold. Si-H in hydrogen-containing silicone oil can interact with other molecules containing active groups at low temperatures to form a cross-linked structure, thereby ensuring the application effect of the release agent in different environments. Dimethyl silicone oil and hydrogen-containing silicone oil not only show good lubricity and chemical resistance, but also have good high temperature stability and low temperature self-crosslinking properties, so that the formed release agent has good weather resistance. The emulsifier can form a stable system in the release agent, ensuring that the release agent has uniform composition and no precipitation and stratification during use, transportation or storage. A non-ionic emulsifier and an ionic emulsifier are compounded, wherein the anionic emulsifier is ionized in water to generate electric charge, so that the surface of the emulsified tiny oil droplets has the same charge. According to the principle of like charges repel each other, the electrostatic effect prevents the oil droplets from agglomerating, thereby effectively improving the stability of the emulsion.

[0009] Optionally, the emulsifier comprises the following raw materials in percentage by weight: 23.5-25% Span-80, 21-23% triethanolamine dodecylbenzenesulfonate, 26.5-32% OP-10, 10-14.5% inulin-modified hydrogenated silicone oil and 10-14.5% alkyl glycoside.

[0010] By adopting the above technical scheme, inulin, also known as inulin, is a natural, pollution-free, abundant and renewable polyfructose. Due to its excellent thickening, solubility and stability, inulin is widely used in various fields. It contains rich hydroxyl groups and therefore has high chemical activity. Allyl glycidyl ether is used to react with hydrogenated silicone oil to introduce epoxy groups into long silicon chains. Then, the hydroxyl groups in inulin react with epoxy groups to hydrophilically modify the hydrogenated silicone oil to prepare inulin-modified hydrogenated silicone oil surfactant. The same inulin-modified hydrogenated silicone oil It contains hydrophilic -OH and lipophilic Si-O-Si chains, so it has an amphiphilic structure and can be adsorbed at the interface of immiscible oil-water phases, so that one phase is evenly dispersed in the other phase, improving the uniformity and stability of the emulsion. Alkyl polyglycoside has a broad-spectrum antibacterial activity, which can further improve the antibacterial and mildew-proof properties of the release agent. Alkyl polyglycoside is a new type of non-ionic surfactant with relatively comprehensive performance. It has a lubricating effect, can improve the demoulding effect of the release agent, reduce the adhesion of concrete on the formwork surface, and increase the stability of the release agent.

[0011] Optionally, the preparation method of the mildew inhibitor is as follows: 1-2 parts by weight of chitosan quaternary ammonium salt, 2-4 parts by weight of nano silver sol and 1000-2000 parts by weight of deionized water are mixed to prepare a mixed solution, which is added dropwise into a sodium dodecyl sulfate solution and stirred evenly, centrifuged, added into deionized water, and freeze-dried. The volume ratio of the mixed solution to the sodium dodecyl sulfate solution is 2-3:1.

[0012] By adopting the above technical scheme, chitosan quaternary ammonium salt, as a derivative of chitosan, carries a large amount of positive charge, sodium dodecyl sulfate is an anionic surfactant with a large amount of negative charge, and the amino group in the chitosan quaternary ammonium salt carries a positive charge, which can be combined with the negatively charged sulfate ions in the sodium dodecyl sulfate through electrostatic action, thereby forming an encapsulation film on the surface of the nanosilver sol, and the nanosilver can release silver ions, thereby interacting with the negatively charged bacterial membrane, resulting in the disintegration of the lipid bilayer structure, promoting the formation of holes on the bacterial membrane, and then the bacterial membrane ruptures and dies, thereby improving the mildew-proof and antibacterial effects of the release agent.

[0013] Optionally, the nanosilver sol contains quaternized nanosilver particles, polyvinyl alcohol, glutaraldehyde and deionized water in a mass ratio of 1:0.3-0.5:0.3-0.5:100.

[0014] By adopting the above technical scheme, the nanosilver sol is composed of quaternary ammonium nanosilver particles stably dispersed in a solution formed by deionized water, polyvinyl alcohol and glutaraldehyde. The polyvinyl alcohol in the nanosilver sol can undergo a cross-linking reaction with the quaternary ammonium salt chitosan through glutaraldehyde, and the quaternary ammonium nanosilver particles can undergo a cross-linking reaction with the polyvinyl alcohol under the action of glutaraldehyde, thereby forming an interpenetrating network, improving the encapsulation rate of the quaternary ammonium salt chitosan and sodium dodecyl sulfate for the nanosilver, and extending the mildew-proof and antibacterial time of the release agent.

[0015] Optionally, the reinforcing component includes water glass, waste glass powder and flake graphite in a mass ratio of 6.5-6.9:3-3.4:0.1.

[0016] By adopting the above technical scheme, waste glass powder is suitable as an isolation material from the perspective of slippery feeling. Flake graphite also has a lubricating effect, which makes concrete less likely to adhere to the formwork and improves the demoulding effect. In addition, the addition of glass powder can improve the surface strength of the test block, balance the negative effect of the release agent on cement hydration, accelerate the cement hydration reaction process, and reduce the porosity. Water glass can penetrate into the pores on the surface of concrete and react with the hydration product calcium hydroxide in the cement to form calcium silicate colloid, which compacts the surface of the concrete, prevents water evaporation, and plays a curing role. The waste glass powder mixed in the water glass can react with the cement when the water glass penetrates, play the role of filling and reaction products, refine the concrete surface, and improve the density and strength of the concrete.

[0017] Optionally, polyisobutylene-modified silica is further added to the reinforcing component, and the mass ratio of polyisobutylene-modified silica to water glass is 1-1.5:6.5-6.9.

[0018] By adopting the above technical scheme, polyisobutylene is a high molecular compound formed by the polymerization of isobutylene, which has excellent hydrophobicity, and its molecular chain is relatively long, which can form a lubricating film to reduce friction and wear, and it also has a good viscosity index and excellent shear stability. Mixing it with silica can improve the hydrophobicity of silica, thereby improving the hydrophobicity of the release agent on the mold surface, improving the adhesion of the release agent, and enhancing the demolding effect. Silica has a high volcanic ash reaction activity and can react with the cement hydration product calcium hydroxide to generate more CSH gel. Secondly, it has a crystal nucleus effect, can act as a crystal nucleus, reduce the nucleation barrier, and deposit more hydration products on its surface. It also has a filling effect to improve the surface hardness of the concrete block.

[0019] Optionally, the preparation method of the polyisobutylene modified silica is as follows: The polydimethylsiloxane and silicon dioxide are mixed, stannous chloride is added, the temperature is raised to 110-120°C, the mixture is stirred for reaction for 3-4 hours, filtered, washed and dried to obtain a mixed powder, wherein the mass ratio of silicon dioxide, stannous chloride and polydimethylsiloxane is 45:0.045:150-200; The polyisobutylene and the mixed powder are blended, kneaded at 130-140° C. for 50-60 minutes, and crushed to obtain polyisobutylene-modified silicon dioxide, wherein the mass ratio of the polyisobutylene to the mixed powder is 4-5:3.

[0020] By adopting the above technical scheme, the terminal epoxy groups on the surface of polydimethylsiloxane react with the hydroxyl groups on the surface of silica, so that the polydimethylsiloxane is medium to the surface of silica, reducing its hydrophilicity, thereby improving the compatibility of silica with polyisobutylene, making it evenly dispersed in polyisobutylene, and silica dispersed in polyisobutylene as physical crosslinking points, interacting with polyisobutylene molecules to form a physical crosslinking structure, thereby improving the structural stability of polyisobutylene-modified silica, improving the structural stability of the release agent after film formation, reducing the damage of the release agent, and reducing the adhesion of concrete.

[0021] Optionally, the particle size of the waste glass powder is ≤45 μm, and the particle size of the flake graphite is ≤1.3 μm.

[0022] By adopting the above technical solution, the particle size of waste glass powder and flake graphite is small, thereby obtaining a certain lubricity and filling effect, increasing the density and lubricity of the release agent after film formation, and reducing the adhesion of concrete.

[0023] Optionally, the thickener is selected from at least one of polyacrylamide, carboxymethyl starch, sodium carboxymethyl cellulose and hydroxypropyl cellulose.

[0024] By adopting the above technical solution, the thickener can adjust the viscosity of the release agent, making it easier to apply and control, improve viscosity and adhesion, and enhance the demoulding effect. It can also prevent the release agent from precipitation and stratification during storage and use, thereby improving stability.

[0025] In a second aspect, the present application provides a method for preparing a high-performance mildew-proof release agent for concrete, using the following technical solution: A method for preparing a high-performance mildew-proof release agent for concrete comprises the following steps: The anti-mildew release agent is prepared by mixing dimethyl silicone oil, hydrogen silicone oil, paraffin, emulsifier, anti-mildew agent, reinforcing component, thickener and water relatively evenly.

[0026] In summary, this application has the following beneficial effects: 1. Since the present application adopts polydimethylsilicone oil and hydrogenated silicone oil as the main ingredients of the release agent, and uses Span-80, triethanolamine dodecylbenzenesulfonate, and OP-10 as emulsifiers, the dispersibility of the oil droplets can be improved, making it difficult to produce stratification and precipitation during storage and use.

[0027] 2. In the present application, it is preferred to add inulin-modified hydrogenated silicone oil and alkyl glycoside to the emulsifier, which can further improve the stability and uniformity of the release agent emulsion, increase the antibacterial property and demoulding effect of the release agent, and reduce the adhesion amount of concrete.

[0028] 3. In the present application, quaternary ammonium salt chitosan and sodium dodecyl sulfate are preferably used as coating films, nanosilver is used as a sustained-release antibacterial component, and quaternized nanosilver, polyvinyl alcohol and glutaraldehyde are used as nanosilver sols to increase the encapsulation rate of nanosilver and improve the long-term antibacterial effect.

[0029] 4. In the present application, water glass, waste glass powder and flake graphite are preferably used as reinforcing components, which can improve the lubricity of the release agent, reduce the viscosity of concrete, and increase the surface strength of concrete. In addition, a certain amount of polyisobutylene is added to improve silica, which can further increase the hydrophobicity of the release agent after film formation, reduce the adhesion of concrete, and improve the surface strength of the concrete test block. DETAILED DESCRIPTION

[0030] The following examples further illustrate the present application in detail.

[0031] Preparation Example 1-6 of Antifungal Agent Preparation Example 1: 2 g of chitosan quaternary ammonium salt was added to deionized water to prepare a solution A with a concentration of 1 g / L, and 4 g of nano silver sol was added and mixed uniformly to prepare a mixed solution; The sodium dodecyl sulfate solution was dissolved in deionized water to prepare a sodium dodecyl sulfate solution with a concentration of 2 g / L. The mixed solution was added dropwise to the sodium dodecyl sulfate solution at a rate of 10 mL / h, stirred for 30 min, centrifuged at 10000 r / min for 3 min, the supernatant was discarded, deionized water was added to resuspend the product, the centrifugation was repeated, and finally the product was resuspended in deionized water and freeze-dried for 24 h. The volume ratio of the mixed solution to the sodium dodecyl sulfate solution was 3:1. The nanosilver sol was selected from Yunshen (Fujian) Environmental Protection Technology Co., Ltd., model Ag-CH20, and the concentration was 1000 ppm.

[0032] Preparation Example 2: 1 g of chitosan quaternary ammonium salt was added to deionized water to prepare a solution A with a concentration of 1 g / L, and 2 g of nano silver sol was added and mixed evenly to prepare a mixed solution. The nano silver sol was selected from Yunshen (Fujian) Environmental Protection Technology Co., Ltd., the model was Ag-CH20, and the concentration was 1000 ppm; The sodium dodecyl sulfate solution was dissolved in deionized water to prepare a sodium dodecyl sulfate solution with a concentration of 1 g / L. The mixed solution was added dropwise to the sodium dodecyl sulfate solution at a rate of 10 mL / h, stirred for 30 min, centrifuged at 10000 r / min for 3 min, the supernatant was discarded, deionized water was added to resuspend the product, the centrifugation was repeated, and finally the product was resuspended in deionized water and freeze-dried for 24 h. The volume ratio of the mixed solution to the sodium dodecyl sulfate solution was 2:1.

[0033] Preparation Example 3: The difference from Preparation Example 1 is that the nanosilver sol is prepared by mixing 1g of quaternized nanosilver particles, 0.5g of polyvinyl alcohol-1788, 0.5g of glutaraldehyde and 100g of deionized water. The preparation method of the quaternized nanosilver particles is as follows: 2g of nanosilver particles are added to a solution prepared by mixing 100mL of ethanol and water in a volume ratio of 1:1, ultrasonically dispersed for 30min, 3mL of silane coupling agent KH570 is added, stirred for 24h, centrifuged, precipitated, repeatedly washed with deionized water, and dried. The particle size of the nanosilver particles is 80nm, and the model is CST-NP-S80.

[0034] Preparation Example 4: The difference from Preparation Example 1 is that the nanosilver sol is prepared by mixing 1g of quaternized nanosilver particles, 0.3g of polyvinyl alcohol-1788, 0.3g of glutaraldehyde and 100g of deionized water. The preparation method of the quaternized nanosilver particles is as follows: 2g of nanosilver particles are added to a solution prepared by mixing 100mL of ethanol and water in a volume ratio of 1:1, ultrasonically dispersed for 30min, 3mL of silane coupling agent KH570 is added, stirred for 24h, centrifuged, precipitated, repeatedly washed with deionized water, and dried. The particle size of the nanosilver particles is 80nm, and the model is CST-NP-S80.

[0035] Preparation Example 5: The difference from Preparation Example 3 is that the nanosilver sol is prepared by mixing 1g of nanosilver particles, 0.5g of polyvinyl alcohol-1788, 0.5g of glutaraldehyde and 100g of deionized water. The particle size of the nanosilver particles is 80nm and the model is CST-NP-S80.

[0036] Preparation Example 6: The difference from Preparation Example 1 is that the nanosilver sol is prepared by mixing 1g of quaternary ammonium nanosilver particles and 100g of deionized water. The preparation method of the quaternary ammonium nanosilver particles is as follows: 2g of nanosilver particles are added to a solution prepared by mixing 100mL of ethanol and water in a volume ratio of 1:1, ultrasonically dispersed for 30min, added with 3mL of silane coupling agent KH570, stirred for 24h, centrifuged, precipitated, repeatedly washed with deionized water, and dried. The particle size of the nanosilver particles is 80nm, and the model is CST-NP-S80.

[0037] Preparation Example 7 of Inulin-modified Hydrogenated Silicone Oil Preparation Example 7: 0.025 mol of hydrogenated silicone oil with a hydroxyl content of 5%, 0.03 mol of allyl glycidyl ether, and 30% by mass of isopropanol solution were uniformly mixed, nitrogen was introduced, and the temperature was raised to 80° C., and 0.003% by mass of aluminum platinum catalyst was added, and the mixture was reacted at 80° C. for 4 h, and then the isopropanol solvent and unreacted allyl glycidyl ether were removed by reduced pressure rotary distillation at 100° C. to obtain an intermediate; The intermediate was ultrasonically mixed with 5 g of N, N-dimethylformamide and 10 g of isopropanol, and 4.05 g (0.025 mol) of inulin, 20 g of deionized water and 0.15 g of sodium hydroxide were added. After stirring at room temperature for 30 min, the temperature was raised to 90 ° C and the reaction was kept at a constant temperature for 4 h. A cationic resin was added to adjust the pH value to neutral, and the resin in the solution was removed by suction filtration. The filtrate was then subjected to reduced pressure rotary distillation at 100 ° C to remove the solvent to obtain inulin-modified hydrogenated silicone oil. Example

[0038] Example 1: A high-performance mildew-proof release agent for concrete, the raw material dosage is as shown in Table 1, wherein dimethyl silicone oil is selected from Guangzhou Ruicheng Chemical, model PMX-200, hydrogen-containing silicone oil is selected from Guangzhou Yingrun Chemical Co., Ltd., model MHX-1107, the emulsifier includes 23.5% Span-80, 21% dodecylbenzenesulfonic acid triethanolamine salt, 55.5% OP-10, the mildew inhibitor is methylisothiazolinone, the reinforcing component is calcium carbonate, and the thickener is polyacrylamide, which is selected from Gongyi Shengshi Water Purification Materials, model ss-pam-016.

[0039] The method for preparing the high-performance mildew-proof release agent for concrete comprises the following steps: The anti-mildew release agent is prepared by mixing dimethyl silicone oil, hydrogen silicone oil, paraffin, emulsifier, anti-mildew agent, reinforcing component, thickener and water relatively evenly.

[0040] Table 1 Amount of raw materials used in the mildew-proof release agent in Examples 1-3 Raw material / kg Example 1 Example 2 Example 3 Dimethicone 20 15 10 Hydrogen silicone oil 20 15 10 paraffin 8 6 4 Emulsifier 4 3 2 Antifungal agent 4 3 1 Reinforcement components 5 4 3 Thickener 5 4 2 water 50 40 30 Example 2: A high-performance mildew-proof release agent for concrete, the raw material dosage is as shown in Table 1, wherein dimethyl silicone oil is selected from Guangzhou Ruicheng Chemical, model PMX-200, hydrogen-containing silicone oil is selected from Guangzhou Yingrun Chemical Co., Ltd., model MHX-1107, the emulsifier includes 25% Span-80, 23% dodecylbenzenesulfonic acid triethanolamine salt, 52% OP-10, the mildew inhibitor is methylisothiazolinone, the reinforcing component is calcium carbonate, and the thickener is polyacrylamide, which is selected from Gongyi Shengshi Water Purification Materials, model ss-pam-016.

[0041] The method for preparing the high-performance mildew-proof release agent for concrete comprises the following steps: The anti-mildew release agent is prepared by mixing dimethyl silicone oil, hydrogen silicone oil, paraffin, emulsifier, anti-mildew agent, reinforcing component, thickener and water relatively evenly.

[0042] Example 3: A high-performance mildew-proof release agent for concrete, the raw material dosage is as shown in Table 1, wherein dimethyl silicone oil is selected from Guangzhou Ruicheng Chemical, model PMX-200, hydrogen-containing silicone oil is selected from Guangzhou Yingrun Chemical Co., Ltd., model MHX-1107, the emulsifier includes 23.5% Span-80, 23% dodecylbenzenesulfonic acid triethanolamine salt, 53.5% OP-10, the mildew inhibitor is methylisothiazolinone, the reinforcing component is calcium carbonate, and the thickener is polyacrylamide, which is selected from Gongyi Shengshi Water Purification Materials, model ss-pam-016.

[0043] The method for preparing the high-performance mildew-proof release agent for concrete comprises the following steps: The anti-mildew release agent is prepared by mixing dimethyl silicone oil, hydrogen silicone oil, paraffin, emulsifier, anti-mildew agent, reinforcing component, thickener and water relatively evenly.

[0044] Example 4: A high-performance mildew-proof release agent for concrete, which differs from Example 1 in that the emulsifier comprises the following raw materials in percentage by mass: 23.5% Span-80, 21% triethanolamine dodecylbenzenesulfonate, 26.5% OP-10, 14.5% inulin-modified hydrogenated silicone oil and 14.5% alkyl glycoside, the inulin-modified hydrogenated silicone oil is prepared by Preparation Example 7, and the alkyl glycoside is selected from Flower King, model APG0814.

[0045] Example 5: A high-performance mildew-proof release agent for concrete, which differs from Example 1 in that the emulsifier comprises the following raw materials in percentage by mass: 25% Span-80, 23% triethanolamine dodecylbenzenesulfonate, 32% OP-10, 10% inulin-modified hydrogenated silicone oil and 10% alkyl glycoside, the inulin-modified hydrogenated silicone oil is prepared by Preparation Example 7, and the alkyl glycoside is selected from Flower King, model APG0814.

[0046] Example 6: A high-performance mildew-proof release agent for concrete, which differs from Example 4 in that it contains 23.5% Span-80, 21% triethanolamine dodecylbenzenesulfonate, 26.5% OP-10, and 29% inulin-modified hydrogenated silicone oil, and the inulin-modified hydrogenated silicone oil is prepared by Preparation Example 7.

[0047] Example 7: A high-performance mildew-proof release agent for concrete, which is different from Example 4 in that it contains 23.5% Span-80, 21% triethanolamine dodecylbenzenesulfonate, 26.5% OP-10, and 29% alkyl glycoside, and the alkyl glycoside is selected from Flower King, model APG0814.

[0048] Example 8: A high-performance mildew-proof release agent for concrete, which is different from Example 4 in that the mildew-proof agent is made from Preparation Example 1.

[0049] Example 9: A high-performance mildew-proof release agent for concrete, which is different from Example 4 in that the mildew-proof agent is made from Preparation Example 2.

[0050] Example 10: A high-performance mildew-proof release agent for concrete, which is different from Example 8 in that the mildew-proof agent is made from Preparation Example 3.

[0051] Example 11: A high-performance mildew-proof release agent for concrete, which is different from Example 8 in that the mildew-proof agent is made from Preparation Example 4.

[0052] Example 12: A high-performance mildew-proof release agent for concrete, which is different from Example 8 in that the mildew-proof agent is made from Preparation Example 5.

[0053] Example 13: A high-performance mildew-proof release agent for concrete, which is different from Example 8 in that the mildew-proof agent is made from Preparation Example 6.

[0054] Example 14: A high-performance anti-mildew release agent for concrete, which differs from Example 10 in that the reinforcing component includes water glass, waste glass powder and flake graphite in a mass ratio of 6.9:3:0.1, the waste glass powder is made from discarded glass bottles that are washed, dried, crushed and ground to a particle size of 325 mesh, and the particle size of the flake graphite is 1.3 μm.

[0055] Example 15: A high-performance anti-mildew release agent for concrete. The difference from Example 10 is that the reinforcing component includes water glass, waste glass powder and flake graphite in a mass ratio of 6.5:3.4:0.1, the waste glass powder is made from discarded glass bottles by washing, drying, crushing and grinding to a particle size of 325 mesh, and the particle size of the flake graphite is 1.3 μm.

[0056] Example 16: A high-performance mildew-proof release agent for concrete. The difference from Example 14 is that the reinforcing component includes water glass and waste glass powder in a mass ratio of 6.5:3.4, and the waste glass powder is made from discarded glass bottles that are washed, dried, crushed, and ground to a particle size of 325 mesh.

[0057] Example 17: A high-performance mildew-proof release agent for concrete, which differs from Example 14 in that the reinforcing component includes water glass and flake graphite in a mass ratio of 6.5:0.1, and the particle size of the flake graphite is 1.3 μm.

[0058] Example 18: A high-performance mildew-proof release agent for concrete, which is different from Example 14 in that polyisobutylene-modified silica is further added to the reinforcing component, the mass ratio of polyisobutylene-modified silica, water glass, waste glass and flake graphite is 1.5:6.9:3:0.1, and the preparation method of polyisobutylene-modified silica is as follows: Mix polydimethylsiloxane and 45g of silicon dioxide, add 0.045g of stannous chloride, heat to 110°C, stir and react for 4h, then add toluene solvent, the added toluene liquid level is higher than the reactant, shake and evenly mix, let stand for 6h, filter by suction, wash with anhydrous ethanol 5 times, and dry at 80°C for 24h to obtain a mixed powder, the mass ratio of silicon dioxide, stannous chloride and polydimethylsiloxane is 45:0.045:150; The polyisobutylene and the mixed powder were blended, kneaded at 140° C. for 50 minutes, and crushed to obtain polyisobutylene-modified silica. The mass ratio of the polyisobutylene to the mixed powder was 5:3.

[0059] Example 19: A high-performance mildew-proof release agent for concrete, which is different from Example 14 in that polyisobutylene-modified silica is further added to the reinforcing component, the mass ratio of polyisobutylene-modified silica, water glass, waste glass and flake graphite is 1:6.5:3:0.1, and the preparation method of polyisobutylene-modified silica is as follows: Mix polydimethylsiloxane and 45g of silicon dioxide, add 0.045g of stannous chloride, heat to 120°C, stir and react for 3h, then add toluene solvent, the added toluene liquid level is higher than the reactant, shake and evenly mix, let stand for 6h, filter by suction, wash with anhydrous ethanol 5 times, and dry at 80°C for 24h to obtain a mixed powder, the mass ratio of silicon dioxide, stannous chloride and polydimethylsiloxane is 45:0.045:200; The polyisobutylene and the mixed powder were blended, kneaded at 130° C. for 60 minutes, and crushed to obtain polyisobutylene-modified silica. The mass ratio of the polyisobutylene to the mixed powder was 4:3.

[0060] Comparative Example Comparative Example 1: A high-performance mildew-proof release agent for concrete, which differs from Example 1 in that the emulsifier is only Span-80.

[0061] Comparative Example 2: A high-performance mildew-proof release agent for concrete, which differs from Example 1 in that the emulsifier is only OP-10.

[0062] Comparative Example 3: A safe and environmentally friendly concrete release agent, wherein the raw materials are composed of 20 parts of fly ash, 15 parts of paraffin, 2 parts of sodium benzoate, 20 parts of ethanol, and 60 parts of water in the following weight parts.

[0063] Comparative Example 4: A commercially available release agent, selected from Dongguan Anran Industrial, with a product number of BDL3318.

[0064] Performance testing The release agent was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following method. The test results are recorded in Table 3.

[0065] 1. Stability: According to GB / T11543-2008 "Test method for properties of medium and high viscosity surfactant emulsions and evaluation method for their emulsification ability", the release agent stock solution and water are mixed at a mass ratio of 1:10 according to the reaction conditions, and the obtained release agent emulsion is injected into a centrifuge tube. The speed of the centrifuge is set to 4000r / min, and the centrifugation time is 10min. According to the results in Table 2, the uniformity is evaluated and divided into grades, among which grade 1 has the best uniformity and grade 6 has the worst.

[0066] 2. Fungus resistance (inhibition rate): After initial storage and 30 days at room temperature, the product was tested in accordance with GB / T4789-10-2003 "Microbiological Examination of Food Hygiene - Examination of Staphylococcus aureus".

[0067] 4. Adhesion amount on the board surface and surface hardness of the test block: 450g of P·I type 42.5 cement with a specific surface area of ​​357m 2 / kg, the fine aggregate is ISO standard sand, the fineness modulus is 2.6mm, the maximum particle size is 2mm, the mud content is less than 0.2%, and 22.5g of the high-performance mildew-proof release agent prepared in the embodiment or the comparative example is added, and the water-cement ratio is 0.5 to make a mortar liquid. Before the test, the mold is thoroughly cleaned, the rust on the mold is removed with sandpaper, and the release agent to be tested is evenly applied, and then the mortar liquid is poured into the mold that has been coated with the release agent and dried to form a film. After curing for 1d, demoulding is performed, and the adhesion of the mortar on the mold and the surface hardness of the test block after demoulding are observed. The board surface adhesion is calculated according to JC / The release agent of the control ratio is tested according to the standard of T949-2005. The surface hardness of the test block is tested with a Leeb hardness tester. The steps are as follows: Place the test block flat on the ground to ensure absolute stability without any shaking. Then turn on the hardness tester to test the test point. Each test point is tested three times. The hardness value displayed is the surface hardness of the test point of the test block. During this process, the stability of the impact device must be maintained, and the direction should also be kept perpendicular to the tested surface. Each test block is tested at 20 points, and the distance between two test points is ≥3mm. After the test, the average value is taken as the surface hardness of the test block.

[0068] Table 2 Release agent test stability level Stability level / grade Emulsion appearance and stability 1 Good uniformity 2 Initially, uneven consistency can be seen 3 Uneven clarity 4 Initial phase separation is visible 5 Phase separation is clearly visible 6 Complete separation of the two phases Table 3 Performance test results of release agent It can be seen from the data in Table 2 that the release agents prepared by using Span-80, triethanolamine dodecylbenzenesulfonate and OP-10 as emulsifiers in Examples 1-3 still have good storage stability after being stored at room temperature for 12 months, and have good mildew resistance and ideal demoulding effect, and are not easy to adhere to concrete.

[0069] In Example 4 and Example 5, inulin-modified hydrogenated silicone oil and alkyl glycoside are further added to the emulsifier. From the comparison of the data in Table 3, it can be seen that the stability of the release agents prepared in Example 4 and Example 5 is better than that in Example 1, and can still reach Level 2 after 12 months, and the antibacterial property is increased, and the anti-mildew effect is enhanced.

[0070] In Example 6, compared with Example 4, no alkyl polyglycoside was added to the emulsifier, the antibacterial effect of the release agent decreased, the stability became worse, and the adhesion amount on the mold surface increased slightly.

[0071] In Example 7, compared with Example 4, no inulin-modified hydrogenated silicone oil was added to the emulsifier. It can be seen that the stability of the release agent was weakened and the amount of adhesion on the template surface was increased.

[0072] In Example 8 and Example 9, the mildew-proof agents prepared in Preparation Example 1 and Preparation Example 2 were used respectively. Table 2 shows that the release agents have good stability, are not prone to stratification and deterioration, and have more prominent mildew-proof effects.

[0073] In Example 10 and Example 11, the mildew-proofing agents prepared in Preparation Example 3 and Preparation Example 4 were used respectively. Compared with Example 8, it can be seen that the mildew-proofing effect of the release agent is further improved after being stored for half a year.

[0074] In Example 12 and Example 13, the mildew-proofing agents prepared in Preparation Example 5 and Preparation Example 6 were used respectively. As shown in Table 3, compared with Example 8, the mildew-proofing effect was further improved, but compared with Example 10 and Example 11, the mildew-proofing effect was reduced.

[0075] Compared with Example 10, Examples 14 and 15 also use water glass, waste glass powder and flake graphite as reinforcing components. Table 3 shows that the release agents prepared in Examples 14 and 15 increase the surface hardness of the test block, indicating that the reinforcing components can improve the mechanical strength of the cement mortar without affecting the demolding effect, and the amount of adhesion on the template surface is reduced.

[0076] Compared with Example 14, Example 16 uses water glass and waste glass powder as reinforcing components. As can be seen from Table 3, the surface hardness of the sample increases, but the adhesion amount on the template surface increases, and the demolding effect is affected.

[0077] In Example 17, water glass and flake graphite are used as reinforcing components. Compared with Example 14, after using the release agent prepared in Example 17, the adhesion amount on the template surface does not change much, but the surface hardness of the test block decreases significantly.

[0078] Compared with Example 14 in Example 18 and Example 19, polyisobutylene-modified silica is further added to the reinforcing component, which improves the surface hydrophobicity of the release agent, reduces the amount of mortar adhesion on the template surface, and further increases the surface hardness of the test block.

[0079] Comparative Examples 1 and 2 respectively use only Span-80 and OP-10 as emulsifiers. Compared with Example 1, the stability of the release agents prepared in Comparative Examples 1 and 2 is significantly reduced.

[0080] Comparative Example 3 is a release agent provided in the prior art, and Comparative Example 4 is a commercially available release agent. Comparison of the data in Table 3 shows that the stability of the release agents in Comparative Examples 3 and 4 is not as good as that of the present application.

[0081] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-performance mildew-proof release agent for concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 10-20 parts of dimethyl silicone oil, 10-20 parts of hydrogenated silicone oil, 4-8 parts of paraffin wax, 2-4 parts of emulsifier, 1-4 parts of mildewproof agent, 3-5 parts of reinforcing component, 2-5 parts of thickener and 30-50 parts of water, wherein the emulsifier comprises the following raw materials in parts by weight: 23.5-25% of Span-80, 21-23% of triethanolamine dodecylbenzenesulfonate and the balance of OP-10.

2. The high-performance mildew-proof release agent for concrete according to claim 1, characterized in that: The emulsifier comprises the following raw materials in percentage by mass: 23.5-25% Span-80, 21-23% triethanolamine dodecylbenzenesulfonate, 26.5-32% OP-10, 10-14.5% inulin-modified hydrogenated silicone oil and 10-14.5% alkyl glycoside.

3. The high-performance mildew-proof release agent for concrete according to claim 1, characterized in that: The preparation method of the mildew inhibitor is as follows: 1-2 parts by weight of chitosan quaternary ammonium salt, 2-4 parts by weight of nano silver sol and 1000-2000 parts by weight of deionized water are mixed to prepare a mixed solution, which is added dropwise into a sodium dodecyl sulfate solution and stirred evenly, centrifuged, added into deionized water, and freeze-dried. The volume ratio of the mixed solution to the sodium dodecyl sulfate solution is 2-3:

1.

4. The high-performance mildew-proof release agent for concrete according to claim 3, characterized in that: The nano silver sol contains quaternized nano silver particles, polyvinyl alcohol, glutaraldehyde and deionized water in a mass ratio of 1:0.3-0.5:0.3-0.5:

100.

5. The high-performance mildew-proof release agent for concrete according to claim 1, characterized in that: The reinforcing components include water glass, waste glass powder and flake graphite in a mass ratio of 6.5-6.9:3-3.4:0.

1.

6. The high-performance mildew-proof release agent for concrete according to claim 5, characterized in that: The reinforcing component is further added with polyisobutylene-modified silica, and the mass ratio of polyisobutylene-modified silica to water glass is 1-1.5:6.5-6.

9.

7. The high-performance mildew-proof release agent for concrete according to claim 6, characterized in that: The preparation method of the polyisobutylene modified silica is as follows: The polydimethylsiloxane and silicon dioxide are mixed, stannous chloride is added, the temperature is raised to 110-120°C, the mixture is stirred for reaction for 3-4 hours, filtered, washed and dried to obtain a mixed powder, wherein the mass ratio of silicon dioxide, stannous chloride and polydimethylsiloxane is 45:0.045:150-200; The polyisobutylene and the mixed powder are blended, kneaded at 130-140° C. for 50-60 minutes, and crushed to obtain polyisobutylene-modified silicon dioxide, wherein the mass ratio of the polyisobutylene to the mixed powder is 4-5:

3.

8. The high-performance mildew-proof release agent for concrete according to claim 5, characterized in that: The particle size of the waste glass powder is ≤45 μm, and the particle size of the flake graphite is ≤1.3 μm.

9. The high-performance mildew-proof release agent for concrete according to claim 1, characterized in that: The thickener is selected from at least one of polyacrylamide, carboxymethyl starch, sodium carboxymethyl cellulose and hydroxypropyl cellulose.

10. The method for preparing the high-performance mildew-proof release agent for concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: The anti-mildew release agent is prepared by mixing dimethyl silicone oil, hydrogen silicone oil, paraffin, emulsifier, anti-mildew agent, reinforcing component, thickener and water relatively evenly.

Citation Information

Patent Citations

  • Oily solid releasing agent and preparation method thereof

    CN103450995A

Cited By

  • Concrete release agent and preparation method thereof

    CN120944616A

  • Surface-reinforced concrete release agent and preparation method thereof

    CN121780234A